(untitled) (Revista Apotheke, 2023)
This experience reportis center edonth e analysis of a formative episode about the production processof a book-work as an object of study during the de gree in Visual Arts. It is proposedtodiscuss the action of reflection in relation the construction of professional teaching know ledge. From a theoretical point of view, the studies are based on the autobiographicalmethod, basing the present investigation from Bueno (2002). To carry out this research, the narrative of a formative episode of an artist’s book constructed to report the professional choice as a student of de gree in Visual Arts wasused. Based on the analysis presented, the relevance of subjectivity as a way of constructing and reconstructing know ledgecanbeseen. It high lights the importance of proposals and training action scapable of relating the theory to the life history of the subject-participants.